2020
DOI: 10.5296/jpag.v10i2.16719
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Employment Policy and Their Impact on Social Integration: Evidence From Nigeria

Abstract: Scholars have long sought answers for the socio-economic and political discomfort of immigrants. Migrants became underclass and exploited in their new environment. In a field survey conducted in Ondo State, Nigeria, the study examined the ontological submissions about immigrants’ plight for employment and the host community’s potentials at tapping high skills available among the migrants. The study anchored on Talcott Parson’s AGIL- Social System Theory of societal survival, most especially its functional prer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Latent in the thesis of this study is the quest to explore the relationship between migration and educational development. As Olaiya (2020) and Skeldon (1997) argued, the relationship between migration and development is complex, multifocal, and yet intuitively simple. To underscore the points in this study, the notion of migration was conceptually defined; neither by the transitional movement of population from rural to urban societies nor by a population-mobility-induced transit from one society (usually economically or politically backward) to a more advanced one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Latent in the thesis of this study is the quest to explore the relationship between migration and educational development. As Olaiya (2020) and Skeldon (1997) argued, the relationship between migration and development is complex, multifocal, and yet intuitively simple. To underscore the points in this study, the notion of migration was conceptually defined; neither by the transitional movement of population from rural to urban societies nor by a population-mobility-induced transit from one society (usually economically or politically backward) to a more advanced one.…”
Section: Resultsmentioning
confidence: 99%
“…Even though education could provide fulcrums for present and future subsistence, contemporary studies have revealed that schools also address the broader condition and needs of children and society in today's complex world (Moscarola & Kalwij, 2018;Kalwij, Alessie, Dinkova, Schonewille, Schors & van der Werf, 2019;Parlinduncan, 2019). While primary and secondary schools are regarded as the vehicle for driving the importance of literacy and numeracy (Xie & Tu, 2019), they also lay foundations in other areas -in spoken language, science, the arts, the humanities, and physical, emotional and moral development and proper integration into immediate society (Olaiya, 2020).…”
Section: Contextmentioning
confidence: 99%